Ancient Mediterranean Incarceration - Larsen, Matthew D. C. (University of California Press, 2025)
A free ebook version of this title is available through Luminos, University of California Press's Open Access publishing program. Visit www.luminosoa.org to learn more. This book examines spaces, practices, and ideologies of incarceration in the ancient Mediterranean basin from 300 BCE to 600 CE. Analyzing a wide range of sources--including legal texts, archaeological finding